Expression of PTEN, Akt and CREB genes in trigeminal ganglia of intractable migraine - Zheyuan Song; Luyao Zhou; Jiasi Li (SLAS Technology)
Migraine is a kind of common clinical headache. Because its etiology is unknown and the curative effect is not very ideal, recent studies have shown that the activation of trigeminal ganglion has a certain impact on the occurrence of migraine. In this paper, the rat migraine model was established by subcutaneous injection of nitroglycerin. Reverse transcription polymerase chain reaction (RT-PCR) and immunohistochemical techniques were used to observe the changes and correlation of the phosphatase and tensin homolog deleted on chromosome ten (PTEN), protein kinase B (Akt) and cAMP response element binding protein (CREB) expressions in trigeminal ganglia of migraine rats at gene and protein levels, respectively, in order to explore the relationship and role of these three genes in the pathogenesis of migraine. It can be seen from the experimental results that after the treatment of nickel carbohydrazide perchlorate (GTN), the expression level of PTEN mRNA in trigeminal ganglion decreased significantly, and it was the lowest at 12 h of GTN, with a value of 0.21. However, over time, PTEN mRNA expression level has rose to 0.44 after GTN24h, reaching the initial level. According to the calculation, PTEN was significantly negatively correlated with Akt protein expression, and its P value was <0.05. The experiment in this paper first proved that the attack rate of migraine in women was higher than that in men, and then proved the relationship between PTEN, Akt and CREB genes in the trigeminal ganglion of migraine.